2011
DOI: 10.1159/000329534
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and the Risk of Contrast-Induced Acute Kidney Injury in Patients Undergoing Percutaneous Coronary Intervention

Abstract: Background: The relationship between preprocedural C-reactive protein (CRP) levels and the incidence of contrast-induced acute kidney injury (CI-AKI) is unknown. Methods: Documents of 7,310 consecutive patients undergoing percutaneous coronary intervention (PCI) were screened. Patients with acute myocardial infarction, cardiogenic shock, concomitant inflammatory conditions or undergoing CABG within 48 h were excluded due to potential confounding effects. Results: A total of 4,522 patients were valid for analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 60 publications
5
47
1
Order By: Relevance
“…The elderly remain at a higher risk of CIN after PCI, a few studies have found age older than 70 years to be an independent predictor of CIN in multivariate analysis. 29 Mehran et al, similarly, found eight variables for patients who underwent PCI (hypotension, intra-aortic balloon pump, congestive heart failure, chronic kidney disease, diabetes, age 75 years, anemia, and volume of contrast) and assigned a weighted integer to each variable to make up a score cumulatively so as to divide low risk (5) and high risk (16) scores. 7 Many studies have found Diabetes Mellitus (DM) as an independent risk factor for CIN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The elderly remain at a higher risk of CIN after PCI, a few studies have found age older than 70 years to be an independent predictor of CIN in multivariate analysis. 29 Mehran et al, similarly, found eight variables for patients who underwent PCI (hypotension, intra-aortic balloon pump, congestive heart failure, chronic kidney disease, diabetes, age 75 years, anemia, and volume of contrast) and assigned a weighted integer to each variable to make up a score cumulatively so as to divide low risk (5) and high risk (16) scores. 7 Many studies have found Diabetes Mellitus (DM) as an independent risk factor for CIN.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al in their study demonstrated that elevated preprocedural CRP was associated with an increased risk for CIN in patients undergoing PCI. 16 Lyu et al showed that CRP was a significant and independent predictor of CIN after primary PCI in patients with STEMI. 17 Some studies indicated that the administration of statins was associated with reduced incidence of CIN in patients undergoing PCI and the beneficial effect of statins on systemic inflammation and endothelium dysfunction has been well documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some special populations, such as patients with underlying hypertension, cardiovascular diseases, diabetes mellitus, or preexisting renal insufficiency, the incidence is higher and may be as high as 20-50% [2,3,4]. In patients undergoing coronary angiography in China, the incidence of CI-AKI is 8.7-23.5% [5,6]. The precise mechanisms underlying CI-AKI are not fully understood, especially its cellular and molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] The former one altered oxygen balance leading to medullary hypoxic injury manifesting as cell apoptosis and necrosis. 12,13 The later one initiated the tissue damage through inflammatory factors, [14][15][16] i.e. TNF-A and IL-6.…”
Section: Discussionmentioning
confidence: 99%